2016
DOI: 10.1590/1678-4766e2016022
|View full text |Cite
|
Sign up to set email alerts
|

Variação da composição e abundância das espécies da Classe Appendicularia e seu uso como potenciais bioindicadoras de regiões e massas de água superficiais na área da Bacia de Campos, Rio de Janeiro, Brasil

Abstract: RESUMO Estudos sobre a variação espacial das espécies de apendiculárias e sua relação com as massas de água são raros, principalmente no Atlântico Sul. O atual estudo pretende preencher a lacuna de conhecimento sobre a abundância, composição específica e a função de bioindicadora das apendiculárias, em diferentes regiões (plataforma continental e talude) e massas de água, no Atlântico Sul Ocidental. As coletas foram realizadas no período chuvoso (de fevereiro a abril de 2009) e no período seco (de agosto a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…While no quantitative data on detrital abundance in the Campos Basin are available at present, the concentration of suspended particulate matter was lower in deep water than in shallow water (Pedrosa et al 2006). In our study region, appendicularians (mostly Oikopleura longicauda) are an abundant mesozooplanktonic group, with higher densities in the upper layers (Bonecker et al 2014, Carvalho and Bonecker 2016. A high abundance of appendicularians at 1 m depth implies a high production rate of discarded "houses" (a source of detritus) that can be an important dietary component for Scolecitrichidae copepods Steinberg 1993, Yamaguchi et al 1999).…”
Section: Abundance Occurrence and Vertical Distribution Of Scolecitmentioning
confidence: 83%
“…While no quantitative data on detrital abundance in the Campos Basin are available at present, the concentration of suspended particulate matter was lower in deep water than in shallow water (Pedrosa et al 2006). In our study region, appendicularians (mostly Oikopleura longicauda) are an abundant mesozooplanktonic group, with higher densities in the upper layers (Bonecker et al 2014, Carvalho and Bonecker 2016. A high abundance of appendicularians at 1 m depth implies a high production rate of discarded "houses" (a source of detritus) that can be an important dietary component for Scolecitrichidae copepods Steinberg 1993, Yamaguchi et al 1999).…”
Section: Abundance Occurrence and Vertical Distribution Of Scolecitmentioning
confidence: 83%
“…Appendicularia Oikopleura longicauda is a widely distributed species in tropical and subtropical waters (Esnal, 1999). Thus, Carvalho and Bonecker (2016) characterized the occurrence of Appendicularia in the Caravelas estuary and the adjacent coastal area, and revealed that, although all species are distributed along the coast, only five were recorded in the estuary (Oikopleura rufescens, O. dioica, O. cophocerca, O. fusiformis, and O. longicauda).…”
Section: N° Of Species %mentioning
confidence: 99%